The Motif of the ‘Bloodbath of Toruń’ in Voltairean Writings Concerning the Dissident Question of 1767/68 and the First Partition of Poland - Kordel, Jacek (Kwartalnik Historyczny, 2022)
The ‘Tumult of Toruń’ of 1724, which resulted in the sentencing to death of the mayor and a dozen or so townsmen (the so-called ‘bloodbath’ or ‘bloody court’), brought about a veritable deluge of publications. It has become widely accepted in literature that these writings fundamentally impacted the development in Western public opinion of the notion that eighteenth-century Poland was an intolerant country. In 1767–71, Voltaire placed his pen at the service of the Russian empress, and his propaganda texts provided support for the diplomatic and military offensive of the court of Saint Petersburg in Poland. One of the more significant themes that appeared in the papers commissioned by the Russians and also in the philosopher’s correspondence was that of the ‘Tumult of Toruń’ of July 1724 and the death sentences that were passed against the city’s mayor and a dozen or so townspeople.